Case-based review: primary central nervous system lymphoma - Korfel, Agnieszka (Neurooncol Pract, 2017)
Primary CNS lymphoma (PCNSL) is a rare diffuse large B-cell lymphoma originating within the central nervous system. The overall incidence of PCNSL is rising, particularly in the elderly population. Immunosuppression is a strong risk factor, but most patients with this tumor are apparently immunocompetent. Diagnosis of PCNSL can be challenging. Non-invasive or minimally invasive tests such as ophthalmological evaluation and spinal fluid analysis may be useful, but the majority of patients require tumor biopsy for definitive diagnosis. Our knowledge concerning optimum treatment of PCNSL is fragmentary due to paucity of adequately sized trials. Most patients are now initially treated with high-dose-methotrexate-based chemotherapy alone, as the addition of whole-brain radiotherapy at standard doses has not been shown to increase survival and does increase the risk of neurological toxicity. Ongoing trials are addressing issues such as the roles of reduced-dose radiotherapy, the addition of the CD20 antibody rituximab to chemotherapy, high-dose chemotherapy followed by autologous stem cell transplantation, and maintenance therapy in the primary management of PCNSL.